TEKNIK QUICK CHANGE SEBAGAI DASAR PENCIPTAAN TATA BUSANA NASKAH THE DANCING PRINCESS KARYA CLAUDIA HAAS - Milati, Binti Dewi; Prasetiya, Agus; Wibowo, Philipus Nugroho Hari (Institut Seni Indonesia Yogyakarta, 2022)
Costume is an important part of theatrical performances. Clothing is used as a character's identity and can also reflect the character's character. Quick Change is a method of changing quickly on stage. Quick Change became the basic idea in fashion creation. Script for The Dancing Princess by Claudia Haas is a script that tells the story of the lives of four princesses, who continue to dance because they are magicd by a royal adviser. Analysis of characters and settings is very necessary to create a dress. The Victorian era will be the setting for the place as well as a reference in the creation of fashion with thetechnique Quick Change. Aesthetics will be the basis of theory in the creation of fashion with thetechnique Quick Change. The choice of shape, color, and fashion that is chosen will lead to an aesthetic value objectively. Thetechnique knock down adopted from the science of architects is also one of the methods to create clothing with thetechnique Quick Change. Quick Change is important in theater to improve productions both visually and technically.Keywords : Costume, Quick Change, Knock Down, Victorian, The Dancing Princess